BMI history and risk of incident fatty liver: a population-based large-scale cohort study. Issue 10 (October 2016) - Hashimoto, Yoshitaka; Hamaguchi, Masahide; Fukuda, Takuya; Nakamura, Naoto; Ohbora, Akihiro; Kojima, Takao; Fukui, Michiaki
Abstract : Background and aims: Most physicians might consider that fatty liver would develop along with increasing body weight; however, an association between BMI history and incident fatty liver has not been clarified as yet. Methods: We carried out a population-based cohort study that included 4427 healthy Japanese individuals who received yearly health-checkup programs over a decade. Fatty liver was diagnosed using ultrasonography. Results: During the observational period, 38.7% (case/ N =1002/2588) of men and 17.3% (319/1847) of women were diagnosed with fatty liver. Among these, only 18.9% (189 of 1002 participants) of men and 18.5% (59 of 319) of women developed fatty liver when they reached the lifetime maximum BMI. Adjusted odds ratio of the difference between lifetime maximum BMI and BMI at age 20 years (ΔBMImax−20 years ) for incident fatty liver was 1.33 [95% confidence interval (CI) 1.28–1.39, P <0.001] in men or 1.40 (95% CI 1.33–1.49, P <0.001) in women. According to receiver operator characteristic (ROC) analysis, the optimal cut-off points of ΔBMImax−20 years for incident fatty liver were 4.82 kg/m 2 [area under ROC curve 0.70 (95% CI 0.68–0.72), P <0.001] in men and 4.11 kg/m 2 [area under ROC curve 0.76 (95% CI 0.73–0.79), P <0.001] in women. Conclusion: The ΔBMImax−20 years was associated with an increased risk of incident fatty liver. In addition, more patients developed fatty liver not at the maximum point of BMI history, but after that. Therefore, it is useful to check ΔBMImax−20 years and to continue observing the individuals for detection of fatty liver.